Maerua sebrabergensis (Capparaceae), a new species from Namibia - Swanepoel, Wessel (Phytotaxa, 2015)
Maerua sebrabergensis, here described as a new species, has a restricted range and is only known from the Zebra Mountains within the Kaokoveld Centre of Endemism, northwestern Namibia. Diagnostic characters for M. sebrabergensis include a geoxylic suffrutescent habit (rarely a small tree), simple, alternate leaves, petaliferous flowers with the disc not or only slightly produced and smooth, cylindrical, slightly torulose fruit. A comparison of some of the more prominent morphological features to differentiate between M. sebrabergensis and its possible nearest relative, M. parvifolia, are provided.